Factors Controlling the Change of Soil Erosion Intensity in Mountain Watersheds in Serbia - Manojlović, Sanja; Sibinović, Mikica; Srejić, Tanja; Novković, Ivan; Milošević, Marko V.; Gatarić, Dragica; Carević, Ivana; Batoćanin, Natalija (Frontiers in Environmental Science, 2022)
The intensity of soil erosion is the result of a combined action of natural factors and different human activities. This work aims to determine the factors controlling the change of soil erosion. Eleven watersheds from different parts of Serbia were used as the study area. An Erosion Potential Model was applied to estimate the soil erosion status of the watersheds in two periods, 1971 and 2010. The model indicated that the reduction of soil erosion intensity in the watersheds ranges from 12.4% to 82.7%. The statistical analysis examines quantitative relationships and combined effects between soil erosion and socio-economic and main physical-geographical determinants in watersheds. Watershed characteristics were divided into 5 classes, and within each class 22 variables were calculated: two variables relate to erosion, one to topography, two to land cover, seven to demographic and ten to agrarian variables. Correlation analysis and Principal Component Analysis (PCA) have been applied to understand the main variables that contribute to change soil erosion intensity. The PCA identified four components that can explain at least up to 79.06% of the variation of all variables. This study explores new indicators for correlations with changing soil erosion and provides decision makers with access to quantification for environmental impact assessment and decision-making for adequate soil conservation and management programs.